Determinan Tipe Kepemilikan Rumah Perkotaan di Indonesia: Model Pilihan Kualitatif Menggunakan Data Susenas 2001 - Syahrial, Syarif; Nazara, Suahasil (UI Scholars Hub, 2006)
The development of housing study in Indonesia is relatively behind compared with the progressivity of this study in other countries. This study is a preliminary study on housing sector in Indonesia which concerns with the factors determining the probability of a person to own a house which is also known as housing tenure choice. This study will also reveal the factors that affect the expectation of a household that doesn't own a house to own one. The explanatory variables in this model include age variables, highest educational achievement, and the category of job status of the household head, marital status, number of household members, and access to housing credit (Kredit Pemilikan Rumah) which affects the probability and expectation of a household to own a house. To get the location aspect, we also estimate our model for urban DKI Jakarta, Java with the exception of DK! Jakarta, and Sumatera. The data utilized in this study comes from Indonesia Socioeconomic Survey (SUSENAS) 200I which is the result of Indonesian Statistical Bureau (BPS) survey in all the provinces in Indonesia. This study focuses in urban area in Indonesia and use qualitative choice model in the estimation process. This study also focuses on multiple choices estimation process with logit model. The result shows that the proportion of Indonesian households which live in urban area and own a hose is 73% of the total households which is very big. The proportion of the households with rent/contract is 15.8%. DK! Jakarta has the biggest proportion of households with rent/contract which is about 31.4% The estimation results of urban house ownership choice model in Indonesia show that number of household members, marital status, age of the head of the household, and access to housing credit have (1 positive impact on the probability of a household to own a house (non rent/contract). From the study of the expectation of a household that doesn't own a house to own one we found that only 30% of Indonesian urban households have expectation to own a house for the next five years. Estimation of household expectation function to own a house shows that marital status, education level, income, and head of the household that works in formal sector have positive and significant impacts on the probability of a household to expect to own a house in the next 5 years. One of the most important results concerns KPR and government policy concerning KPR. The Data shows that only 6.37% of the urban households in Indonesia utilize this facility. Down payment and increase in lhe household expenses as a consequence of credit payment are two of the major factors causing low access of the